REVIEW OF TELEREHABILITATION OF PHYSICAL THERAPY (Journal of Pharmaceutical Negative Results, 2022)
Objective: The purpose of the research was to bring together all of the information on telerehabilitation in physical therapy then had gathered through systematic reviews.Methods: Systematic reviews of various illnesses, groups, and situations were included, with the intervention being telerehabilitation by physical therapy. the outcomes were clinical efficacy, functioning, quality of life, happiness, adherence, and safety depending on the conditiona reviewextracted the data and assessed the possibility of biaswith a second reviewer performing non-independent verification. In the tables and figures, the findings are presented qualitatively.Results: There were 53 systematic reviews in total, with 17 of them having a There is a low chance of prejudice. There were fifteen reviews devoted to cardiorespiratory rehabilitation, fourteen to musculoskeletal issues, and thirteen to neurorehabilitation. Other types of conditions and therapy were addressed in the other 11 assessments Thirteen reviews have a low chance of being biassed and found that telerehabilitation was superior to in-person rehabilitation or no therapy, whereas 17 11 found no differences between the groups. Thirty-five reviews with a high or uncertain risk of bias yielded conflicting results. Telerehabilitation is defined as "the delivery of rehabilitation services using information and communication technology." It includes assessment, prevention, therapy, education, and counseling Instead of drugs or surgery, physical therapies such as massage, heat treatment, and exercise are used to treat illness, injury, or deformity.